Pharmacodynamics and Hepatoprotective Properties of Drugs Affecting Metabolic Processes in Patients with Drug-Induced Liver Injury on the Background of Specific Antituberculosis Therapy - Anna V. Berestova (Journal of Global Pharma Technology, 2016)
Objective. Data on pharmacodynamics and hepatoprotective properties of taurine, ursodeoxycholic acid and their combinations in the treatment and prevention of drug-induced liver injury on the background of specific anti-TB therapy is presented. In the study course, a retrospective analysis of primary medical documentation of 270 patients was carried out. Materials and Methods. These patients were undergoing antituberculosis therapy in regional clinical tuberculosis hospitals during 2013-2016. Clinical studies were conducted in the regional clinical tuberculosis hospital in 2016-2018. At the clinical stages, 100 patients were examined. Results and Discussion. A retrospective analysis showed that in a real clinical practice, anti-TB therapy is canceled even with a moderate increase of the transaminase level. Temporary cancellation and correction of specific therapy led to a slowed-down x-ray dynamics and an increase in the length of hospital stay. It also helped to reduce clinical manifestations of liver injury and decreased enzyme activity in most patients for 8-14 days, though the transaminases absolute values remained above the reference values. Conclusion. Taurine intake in dose of 1000 mg/day for the pharmacological correction and prevention of drug-induced liver injury showed high drug efficacy both in monotherapy and combination with ursodeoxycholic acid. Taurine shows an immunomodulatory effect in patients with tuberculosis, with increase of CD3, CD4, CD16, immuno-regulatory index and decrease of CD8, the level of cytokines IL-4, IL-6 and TNF-α.Keywords: Drug-induced liver injury, Specific antituberculosis therapy, Pharmacodynamics, Hepatoprotectors, taurine, Ursodeoxycholic acid.